2016
DOI: 10.1038/ncomms11151
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 regulates PTHrP to coordinate chondrocyte growth, proliferation and differentiation

Abstract: Precise coordination of cell growth, proliferation and differentiation is essential for the development of multicellular organisms. Here, we report that although the mechanistic target of rapamycin complex 1 (mTORC1) activity is required for chondrocyte growth and proliferation, its inactivation is essential for chondrocyte differentiation. Hyperactivation of mTORC1 via TSC1 gene deletion in chondrocytes causes uncoupling of the normal proliferation and differentiation programme within the growth plate, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
108
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(123 citation statements)
references
References 53 publications
10
108
4
1
Order By: Relevance
“…In our 2D and 3DCI assays of Activin-A-stimulated FOP-iMSCs, mTOR inhibitors clearly decreased both GAG/DNA and the expression levels of chondrogenesis markers (Figure 3 and Supplemental Figure 4), indicating that mTOR inhibition did not simply affect proliferation or survival, but modified the differentiation of chondrocytes, since data from both assays were corrected by the number of cells (DNA amount) and the expression of a housekeeping gene (β-actin), respectively. On the other hand, another report showed that hyperactivation of mTORC1 via TSC1 gene deletion in chondrocytes blocked chondrocyte differentiation (72). These reports suggest that a well-coordinated, but complicated, regulation of mTORC1 activity is crucial for chondrocyte differentiation during development.…”
Section: Discussionmentioning
confidence: 97%
“…In our 2D and 3DCI assays of Activin-A-stimulated FOP-iMSCs, mTOR inhibitors clearly decreased both GAG/DNA and the expression levels of chondrogenesis markers (Figure 3 and Supplemental Figure 4), indicating that mTOR inhibition did not simply affect proliferation or survival, but modified the differentiation of chondrocytes, since data from both assays were corrected by the number of cells (DNA amount) and the expression of a housekeeping gene (β-actin), respectively. On the other hand, another report showed that hyperactivation of mTORC1 via TSC1 gene deletion in chondrocytes blocked chondrocyte differentiation (72). These reports suggest that a well-coordinated, but complicated, regulation of mTORC1 activity is crucial for chondrocyte differentiation during development.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study suggested that mTOR signaling in B cells could indirectly regulate osteoclast formation through regulation of ␤-catenin and RANKL/osteoprotegerin (OPG) (9) and another study showed everolimus can restrain the paracrine pro-osteoclast activity of breast cancer cells (19). mTOR signaling may also play an important role in osteoclast survival and differentiation of osteoclast progenitors (8,20,21). In this study, we found that mTORC1 regulates osteoclast differentiation and formation in a cell-autonomous manner with a conditional knockout mice model.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of mTORC1 signaling through the biallelic deletion of Raptor in chondrocytes inhibits chondrocyte functions, leading to impaired skeletal growth (37). In addition, genetic inactivation of the mTORC1 inhibitor TSC1 gene in chondrocytes causes chondrodysplasia in mice (38), suggesting that the fine-tuning of mTORC1 signaling is essential for longitudinal bone growth.…”
Section: Discussionmentioning
confidence: 99%